Online Learning During Covid-19 Outbreak at Islamic Higher Education; The Perceptions of PAI Students in Indonesia - Kaharuddin Kaharuddin; Rahmat Fauzan (P3I Luwu Raya, 2022)
This research aimed to investigate the perceptions of Islamic Education Department (PAI) students on online learning during the Covid-19 outbreak in Indonesia. The involvement of students and teachers in online learning was carefully analyzed by using the Community of Inquiry (CoI) theory. A qualitative phenomenological approach was adopted in this research. Qualitative questionnaires, interviews, and document analysis were conducted by sampling 37 PAI students from 21 different Islamic universities in Indonesia. The research data were analyzed through the stages of data condensation, data display, and data conclusion drawing. The reliability and validity of the data were further accomplished through audio recording and data triangulation. The findings of this research indicated that (1) the students experienced both benefits and challenges in the implementation of online learning during the outbreak. The benefits of using online learning consisted of enhancing students’ IT skills, overcoming costs, facilitating flexible learning, and improving students’ confidence. However, several challenges were also faced by students in terms of poor internet connection, high occurrences of distraction, lack of teacher-student immediacy, and lack of social value. (2) Based on the CoI theory, three elements were investigated in the forms of teaching presence, social presence, and cognitive presence. In teaching presence, five core issues were identified. The issues included teacher preparation, teacher attendance, teacher explanation, teacher interaction, and teacher’s IT skills. In terms of social presence, student communication, student cooperation, and emotional relationship were discussed. In cognitive presence, three issues consisting of building students' cognitive ability, encouraging students' learning curiosity, and facilitating students’ practicum were addressed. This research on online learning is expected to be used as reference for academics in conducting effective online learning for PAI students. In addition, the result of this study could also be used by future researchers in conducting research in the related field.